J09 Physiotherapy Task Orientated Approach: A Case Report. (17th September 2014) - Jones, K; Debono, K; Quinn, L; Rosser, A; Busse, M
Abstract : Background: Impairments in motor learning are evident in people with Huntington's Disease (HD). Exercise and task-specific practice may have potential to promote neuroplastic adaptation and motor learning with resulting functional benefits. This case report outlines a physiotherapy programme in a person with late-stage HD. Case description: ML was a 40 year old female diagnosed with HD 6 yrs prior (CAG repeat 46: TFC 2). Major motor problems at initial assessment included rigidity and bradykinesia. ML was dependent upon carers for all personal and domestic ADL. Mobility was severely limited resulting in self-reported social isolation. Intervention: An eight week (1 h per week) functional, task-orientated approach was implemented with focus upon behavioural change and motivational goal setting. Education and skills training for carers was simultaneous. Outcomes: Functional improvements were noted (UHDRS function 5 to13; Independence score 45 to 55), TFC (2 to 6), with clinically significant improvements in all physiotherapy (blinded assessor) outcome measures (Physical Performance Test (4 to 16), Berg Balance scale (22 to 45), Timed Up and Go (47.2 to 33.3s), 6 min walk (0 to 297.5m) and 10 metre timed walk (0 to 8.47s). ML also reported transfer of these improvements into family and community participation. Discussion: This case provides evidence that people with HD can achieve motor learning leading to functional changes. Integration of the intervention into daily living and the ongoing support and engagement of the carers allowed sufficient intensity of practice, and are deemed to be the major influences in the success of this programme.